Schizothyriaceae - R. Phookamsak (2018)
© Guizhou Academy of Agricultural Sciences. Schizothyriaceae is a poorly understood family which was introduced to accommodate epiphytes belonging to the class Dothideomycetes. Sixteen sexual and asexual genera have at various times been accommodated in Schizothyriaceae. However, modern taxonomic descriptions, molecular data and phylogenetic investigation of the genera in this family are limited. We therefore revisit the genera in Schizothyriaceae by loaning and examining the type and other specimens from herbaria worldwide. Circumscriptions of the genera previously placed in Schizothyriaceae are provided with illustrations and their higher level placements are determined based on modern descriptions. Based on morphology, we currently accept Hexagonella, Lecideopsella, Mycerema, Plochmopeltis and Schizothyrium in Schizothyriaceae. Kerniomyces, Metathyriella and Myriangiella are treated in Schizothyriaceae, genera incertae sedis, while Chaetoplaca is transferred to Ascomycetes, genera incertae sedis. Neopeltella is excluded from Schizothyriaceae, based on its thyriothecial ascomata and tentatively placed in Micropeltidaceae. Henningsiella is placed in Saccardiaceae due to its discoid ascomata. Linopeltis and Orthobellus are tentatively treated in Dothideomycetes, genera incertae sedis. Hysteropeltella which has elongate apothecial or hypothecia-like ascomata, is placed in Patellariaceae due to its similar morphology with Baggea. Mendogia is transferred to the family Myriangiaceae based on a morphologically similar specimen which is phylogenetically placed in Myriangiaceae. The hyphomycetous, Zygophiala is reported as the asexual morph of Schizothyrium. Hence, the genus is currently treated as a synonym of Schizothyrium. Nevertheless, representative species of the genera in Schizothyriaceae, including the type species, need to be recollected and sequenced to clarify the natural placement in Schizothyriaceae.